2020
DOI: 10.1007/s11669-020-00837-x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Assessment of the Al-Ti-Zr System

Abstract: Only within the last couple of years, complete isothermal sections for the Al-Ti-Zr system have been determined. Up to then there had been several investigations, but these were limited to the Ti-Zr and Ti-Al sides and the Ti- and Al corners of the system. Also recently the system has been evaluated by thermodynamic ab initio calculations and CALPHAD-type (CALculation of PHAse Diagrams) modelling. As Al-Ti-Zr alloys are of interest for a variety of applications and as the last assessment has been performed mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 64 publications
(104 reference statements)
2
17
0
Order By: Relevance
“…Additionally, the eutectoid temperature increases upon alloying with Zr, as demonstrated in Figure 12, indicating the stabilization of the α 2 compared to the α phase similar to the cases with Mo and V. [ 228,229 ] At intermediate temperatures, i.e., the temperature range of the α 2 + γ phase field region, sufficient alloying with Zr may cause the formation of the (Zr,Ti) 5 Al 3 phase. [ 225 ] With respect to ternary intermetallic compounds, contradicting results can be found for this system. Some authors claim that no ternary phases are thermodynamically stable in the Ti–Al–Zr system.…”
Section: Effect Of Additional Alloying Elements On the Phase Transfor...mentioning
confidence: 94%
See 2 more Smart Citations
“…Additionally, the eutectoid temperature increases upon alloying with Zr, as demonstrated in Figure 12, indicating the stabilization of the α 2 compared to the α phase similar to the cases with Mo and V. [ 228,229 ] At intermediate temperatures, i.e., the temperature range of the α 2 + γ phase field region, sufficient alloying with Zr may cause the formation of the (Zr,Ti) 5 Al 3 phase. [ 225 ] With respect to ternary intermetallic compounds, contradicting results can be found for this system. Some authors claim that no ternary phases are thermodynamically stable in the Ti–Al–Zr system.…”
Section: Effect Of Additional Alloying Elements On the Phase Transfor...mentioning
confidence: 94%
“…Such a stabilization of the β phase at the expense of α phase is also evidenced by the isothermal sections presented in previous studies. [218,[225][226][227] The contraction of the α single-phase field region is further promoted by the increase of the γ-solvus temperature. In particular, Musi et al [228] reported that Zr stabilizes the γ phase at temperatures below this transition temperature, i.e., the amount of γ increases at the expense of α/α 2 .…”
Section: Zirconiummentioning
confidence: 99%
See 1 more Smart Citation
“…From this assessment, it is clear that discrepancies exist, especially between recent CALPHAD modellings [21,22] and experimentally determined phase equilibria [6,11,[23][24][25]. As pointed out in the assessment [20] as well as in the modellings [21,22], specifically at 800 • C, even the multi-phase equilibria are not settled, e.g., the experiments show TiAl in equilibrium with βTi at 800 • C, while the CALPHAD modellings show equilibria between TiAl and Zr 4 Al 3 [21] or between TiAl and ZrAl 2 [22], which "cut off" any possible phase equilibrium between TiAl and βTi. In consequence, adjacent phase equilibria differ completely from each other within a wide composition range at 800 • C in [20][21][22].…”
Section: Introductionmentioning
confidence: 94%
“…In a first step, a complete assessment of all available literature on phase equilibria in the Ti-Al-Zr system was performed [20]. From this assessment, it is clear that discrepancies exist, especially between recent CALPHAD modellings [21,22] and experimentally determined phase equilibria [6,11,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%